A theoretical approach to describing the employees’ performance in light of some characteristics of the organizational climate - BOULCHERCHE, Kamel (Journal of Human Sciences, 2020)
Creative organizations are those that provide an adequate working environment in which innovation is considered a fundamental and primary objective. They make creative thinking an essential and vital priority among all employees in order to improve their performance; Whereas, noncreative organizations provide a chaotic environment which generates negative behaviors that hinder the performance of the individual, group and the organization in general. So this article tries to clarify and describe the job performance in shade of some of the characteristics of the organizational climate, and that this performance plays a major role in achieving the objectives set at the individual, group or organizational level.